Thermal-bridge assessment in glazing and aluminium frames by thermo-images: a case study - Laignier, Thiago (2018)
This paper presents the experimental analysis and results of a thermographic inspection performed on aluminum window frames of an instructional facility. The investigation was carried out using thermal images to map the energy loss and gains through aluminum window and door frames on several rooms of the building that houses the School of Technology of the Polytechnic Institute of Bragança in Portugal. The results obtained are discussed in detail and a retrofit strategy is proposed based on the thermal analysis.